Marketing digital y desarrollo de productos de la empresa Comisa en Iquitos 2025 - Rodriguez Pinedo, Sergio Enoc (2025)
The purpose of this research was to determine the relationship between virtual marketing and product development in the company Comisa in Iquitos 2025. The study was a basic, quantitative, correlational, non-experimental, cross sectional design. The sample consisted of 59 clients. In the results, it can be seen that in the digital marketing variable, the majority of respondents reported that they always (50.8%), therefore, a certain percentage (31.7%) indicated that almost always, (6.4%) said never, while only a small percentage responded sometimes (6.3%) or almost never (4.8%). This indicates that, according to the established evaluation criteria, the perception of digital marketing is at a high level; therefore, its implementation has been effective in the organisation and it is considered a key tool to improve digital presence and communication with customers. However, those who said never and sometimes suggest that there are still opportunities to strengthen its adoption and improve its effectiveness.